Young Children and Ongoing Child Welfare Services: A Multilevel Examination of Clinical and Worker Characteristics. (May 2021) - Filippelli, Joanne; Lwin, Kristen; Fallon, Barbara; Trocmé, Nico
There is a growing body of research that underscores that young child welfare-involved children are a unique vulnerable subgroup of children. The decision to provide postinvestigation child welfare services is consequential to children's safety and well-being and has fiscal implications for organizations. Despite the potential ramifications of the decision, there is little known about the factors associated with the ongoing services provision for young children. This study uses secondary data analysis of the Canadian Incidence Study of Reported Child Abuse and Neglect 2008 to explore what case and worker factors predict the provision of ongoing child welfare services. Multilevel modeling was used to assess the relationship between independent variables and the decision to provide ongoing services; analyses included 2, 296 children and 555 workers. Case and worker characteristics, including worker training and worker position, predicted ongoing child welfare services suggesting that further research examining the role of what worker characteristics impact child welfare decisions is warranted and essential.